2022
DOI: 10.1097/mog.0000000000000826
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus disease 2019 and the liver

Abstract: Purpose of reviewThe objective of this review is to examine the epidemiology and pathogenesis of liver injury in coronavirus disease 2019 (COVID-19) and the impact of COVID-19 on patients with chronic liver disease (CLD) and liver transplant recipients.Recent findingsAbnormal liver chemistries occur in up to 60% of COVID-19 patients and are typically mild. COVID-19- associated liver injury may be because of direct viral cytopathic effect, immune-mediated damage, hypoxia, drug-induced liver injury (DILI), or ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 112 publications
0
4
0
Order By: Relevance
“…These differences could be attributed to the nature of the studies that were included and the various outcomes definitions[ 207 , 208 ]. It seems that LI portends the need for ICU care and IMV[ 209 ]. CLD is also associated with severity [odds ratio (OR)/relative risk (RR) = 1.48, 1.70][ 208 , 210 - 213 ], and mortality (OR/RR = 1.08, 2.65)[ 208 , 212 , 214 ] while in a few studies such an association was not observed[ 6 , 207 , 215 - 219 ] (Table 1 ).…”
Section: Underlying Diseases Severity Prognosismentioning
confidence: 99%
See 2 more Smart Citations
“…These differences could be attributed to the nature of the studies that were included and the various outcomes definitions[ 207 , 208 ]. It seems that LI portends the need for ICU care and IMV[ 209 ]. CLD is also associated with severity [odds ratio (OR)/relative risk (RR) = 1.48, 1.70][ 208 , 210 - 213 ], and mortality (OR/RR = 1.08, 2.65)[ 208 , 212 , 214 ] while in a few studies such an association was not observed[ 6 , 207 , 215 - 219 ] (Table 1 ).…”
Section: Underlying Diseases Severity Prognosismentioning
confidence: 99%
“…CAID is also associated with increased serum levels of IL-1β, -6, -17, -18, TNF-α, and IFN-γ[ 245 ], and predisposes to a variety of viral or fungal-related diseases[ 246 ]. Despite the increased risk of infection[ 247 ], cirrhotics exhibit a lower risk of acquiring SARS-CoV-2[ 209 , 248 , 249 ], whereas in large population studies patients with CLD are not over-represented[ 250 ]. In patients with CLD, a condition known as acute-on-chronic liver failure (ACLF) is characterized by abrupt hepatic decompensation and extrahepatic organ failures and is linked with a significant short-term mortality[ 251 ].…”
Section: Covid-19 In Different Cld Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cases of abdominal solid organ transplant (SOT) patients affected by COVID‐19 were reported days later 2 . Organ transplantation has been significantly impacted by the COVID‐19 pandemic, with kidney transplantation and living donor programs bearing the brunt of this impact 3–6 . The tightening and easing of restrictions in response to “waves” of infection and the appearance of COVID‐19 variations over the course of 2 years have posed unique challenges for waitlisted patients, transplant recipients, and transplant programs 6 .…”
Section: Introductionmentioning
confidence: 99%